2017
DOI: 10.1158/1538-7445.sabcs16-p6-01-09
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-01-09: MiRNA-200b suppresses triple negative breast cancer metastasis by targeting ARHGAP18 and causing sustained Rho A activation

Abstract: This abstract was not presented at the symposium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We found that miRNA-200b-3p was upregulated in the ovary in the three zebrafish comparisons. The role of this miRNA is not fully understood but it is known to be involved in many human cancers: kidney [81], prostate [82], and breast [83]. It is highly released in the serum of the anovulatory women diagnosed with polycystic ovary syndrome and suggested as a clinical marker [84].…”
Section: Discussionmentioning
confidence: 99%
“…We found that miRNA-200b-3p was upregulated in the ovary in the three zebrafish comparisons. The role of this miRNA is not fully understood but it is known to be involved in many human cancers: kidney [81], prostate [82], and breast [83]. It is highly released in the serum of the anovulatory women diagnosed with polycystic ovary syndrome and suggested as a clinical marker [84].…”
Section: Discussionmentioning
confidence: 99%